Epidemiology of multiresistant Enterococcus avium isolates in a Greek tertiary care hospital. - Papaparaskevas, Joseph; Tassios, Panayotis T; Kalapothaki, Victoria; Avlami, Athina; Legakis, Nicholas J; Vatopoulos, Alkiviadis C (Int J Antimicrob Agents, 2002)
A retrospective survey of the isolation rate of Enterococcus avium during the period March 1994-February 2000 conducted in Laikon General Hospital using the WHONET software, revealed a peak in the isolation rates of this species during March 1995-February 1996. The ten strains isolated during this time were studied further. No glycopeptide resistance was detected but resistance to ampicillin, ciprofloxacin, erythromycin, gentamicin (high-level) and streptomycin (high-level) was present in nine, ten, nine, three and seven of the isolates, respectively. The genes aac(6')-Ie+aph(2")-Ia and ant(6)-I, encoding for high-level gentamicin and streptomycin resistance, respectively, were detected only in the isolates with the corresponding phenotypes. Beta-lactamase production and haemolysis were not detected. There was evidence of ward-, floor- and building-specific distribution among the different aminoglycoside resistance phenotypes. DNA fingerprinting by PFGE grouped six of the ten isolates in a single cluster with 83% similarity, even though they expressed various resistance phenotypes. These results suggest dissemination of resistance genes among both genetically related and unrelated strains.
Keywords: Anti-Bacterial Agents; DNA Fingerprinting; Drug Resistance, Multiple, Bacterial; Enterococcus; Gram-Positive Bacterial Infections; Greece; Hospitals; Humans; Phylogeny; Retrospective Studies